Vibronic coupling and excitation transfer in hydrogen-bonded molecular dimers: a quantum dynamical analysis - Goswami, Sugata; Kopec, Sabine; Köppel, Horst (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2019)
A brief pedagogic rederivation is given of basic exciton coupling theory, taking the nuclear coordinates to be fixed. This is then extended to take variations of these coordinates into account by adopting suitable multimode coupling models and extracting the transfer of excitation energy from the populations of the locally excited states. The dynamical problem thus defined is solved numerically in a fully quantal manner. Two doubly hydrogen bonded dimers of (hetero)aromatic systems are selected as representative cases whose electronic excitation spectra have been analyzed previously based on ab initio data, and good agreement with experiment has been found. The numerical calculations of the electronic populations reveal a complex time dependence of the excitation transfer that is far from being oscillatory or exponential. For localized excitation, the short-time behavior can be understood in terms of the quenched excitonic energy splitting, while for delocalized excitation a complex time dependence with rapidly changing features results. Some of these can be interpreted in terms of the vibronic structure of the excitation spectra. The importance of the quenched excitonic splitting for the short-time behavior of the excitation energy transfer is emphasized.
Gesehen am 22.04.2020